A two-part model to estimate inpatient, outpatient, prescribing and care home costs associated with atrial fibrillation in Scotland. Issue 3 (18th March 2020) - Ciminata, Giorgio; Geue, Claudia; Langhorne, Peter; Wu, Olivia
Abstract : Objective: This study aimed to estimate global inpatient, outpatient, prescribing and care home costs for patients with atrial fibrillation using population-based, individual-level linked data. Design: A two-part model was employed to estimate the probability of resource utilisation and costs conditional on positive utilisation using individual-level linked data. Settings: Scotland, 5 years following first hospitalisation for AF between 1997 and 2015. Participants: Patients hospitalised with a known diagnosis of AF or atrial flutter. Primary and secondary outcome measures: Inpatient, outpatient, prescribing and care home costs. Results: The mean annual cost for a patient with AF was estimated at £3785 (95% CI £3767 to £3804). Inpatient admissions and outpatient visits accounted for 79% and 8% of total costs, respectively; prescriptions and care home stay accounted for 7% and 6% of total costs. Inpatient cost was the main driver across all age groups. While inpatient cost contributions (~80%) were constant between 0 and 84 years, they decreased for patients over 85 years. This is offset by increasing care home cost contributions. Mean annual costs associated with AF increased significantly with increasing number of comorbidities. Conclusion: This study used a contemporary and representative cohort, and a comprehensive approach to estimate global costs associated with AF, taking into account resource utilisation beyond hospital care. While overall costs, considerably affected by comorbidity, did not increase with increasing age, care home costs increased proportionally with age. Inpatient admission was the main contributor to the overall financial burden of AF, highlighting the need for improved mechanisms of early diagnosis to prevent hospitalisations.